Plain Radiographs Have Limited Utility in the Evaluation of Discoid Lateral Meniscus: Original Research - Schlesinger, Reid P.; Rangwani, Sean M.; Patel, Neeraj M. (Journal of the Pediatric Orthopaedic Society of North America, 2023)
Background: Debate persists regarding the utility of plain film radiography in the diagnosis of discoid lateral meniscus, especially in children. The purpose of this study was to assess various radiographic measurements between healthy children and those with discoid lateral meniscus while controlling for other patient characteristics. Methods: Plain radiographs of 55 pediatric patients with discoid lateral meniscus were matched by age and sex to 55 controls with healthy knees as verified by magnetic resonance imaging. Each radiograph was evaluated for the following parameters: lateral joint space height (both in the central and medial portions of the compartment), medial joint space height, fibular head height, lateral tibial spine height, femoral inter-epicondylar distance, lateral tibial plateau obliquity, and chordal distance of the femoral condyle (medial and lateral). Results: In univariate analysis, children with discoid lateral meniscus had higher median lateral joint space heights (p<0.001) and lower fibular head height (p=0.001) than controls. No other radiographic measurements were significantly different. When adjusting for covariates in regression analysis, the presence of discoid lateral meniscus was predictive of a higher lateral joint space heights and lower fibular head height, however, age was also significantly predictive in these models. Conclusions: On plain radiographs, lateral joint space heights and fibular head height are associated with discoid lateral meniscus. However, many previously reported measurements were not predictive. The practical utility of these parameters may be complicated by the impact of age. Advanced imaging is recommended to confirm the diagnosis of discoid lateral meniscus.